Three weeks of environmental enrichment enhance hepatic-muscular oxidative balance and decrease interleukin-6 levels in juvenile female C57BL/6 mice - Eduarda da Silva Fidélis, Débora; Santos de Sousa Fernandes, Matheus; Ramos, Tiago Lacerda; Gonçalves Silva, Clarice Beatriz; Perreira, Allifer Rosendo; Giselle de Olivera Nóbrega, Cássia; Oliveira de Souza, Valdênia Maria; Yagin, Fatma Hilal; Aygun, Yalin; Lagranha, Claudia Jacques; Fernandes, Mariana Pinheiro; Alwhaibi, Reem M.; et al. (Frontiers in Physiology, 2025)
IntroductionThe Environmental Enrichment (EE) promotes systemic responses through social, cognitive, sensory, and physical stimuli. However, its effects on hepatic and muscle oxidative balance, as well as on serum inflammation markers, remain unclear. Therefore, this study aimed to evaluate whether three weeks of EE could modulate hepatic and muscular oxidative balance and the inflammatory response in female C57BL/6 mice.MethodsThe animals were divided into two groups: EE (n = 13) and Standard Environmental (SE, n = 11) from postnatal day 35 to 60. The EE setting included inanimate objects such as tunnels, ladders, and toys made of both wood and plastic. After three weeks, the mice were euthanized for the withdrawal of the liver, extensor digitorum longus (EDL), soleus, and blood samples.Results and discussionEE significantly reduced body weight and malondialdehyde levels in the liver, soleus, and EDL muscles. Additionally, carbonyl levels decreased in the liver and soleus. Acute EE exposure enhanced enzymatic antioxidant activity (SOD, CAT, and GST) across all tissues, except for catalase activity in the EDL, which showed no significant difference between groups. Non-enzymatic defenses were improved, with reduced oxidized glutathione (GSSG) levels in the liver and soleus. Furthermore, EE increased the REDOX status in the liver and EDL. Sulfhydryl levels increased only in the liver. Finally, serum cytokine analysis revealed a significant reduction only in IL-6 levels. These findings suggest that three weeks of EE can modulate hepatic and muscular oxidative balance, as well as serum IL-6 levels, in juvenile female mice.